Spike Glycoprotein 1 Partial Gene Analysis of GI-19 (QX-like) Infectious Bronchitis Virus Isolated and Propagated from Breeder, Broiler, and Layer Chickens in Java Region - Santoso, Ferdinand Prayogo Cahyo; Widayanti, Rini; Widyarini, Sitarina; Wibowo, Michael Haryadi (HAYATI Journal of Biosciences, 2024)
This study aims to identify and characterize receptor binding sites (RBS) and antigenic sites (HVR-I and II) of the S1 gene fragment of the infectious bronchitis virus (IBV) isolated and propagated from commercial chickens in Java Region to monitor recent circulating virus. The samples in this study were the organs which indicated infectious bronchitis infection. The stages of this research consisted of making virus suspensions, isolation, and propagation, as well as molecular detection and characterization of viruses. Virus isolation and propagation were carried out on chicken embryonated eggs aged 11 days via the allantoic route. Culture confirmation was performed by RT-PCR of the S1 gene fragment, followed by sequencing and bioinformatics analysis. The 168-hour propagation was observed in both dwarfed and curled embryos of two isolates from 11 isolates detected as IBV-positive. Phylogenetic tree construction resulted in all isolates being grouped as GI-19 genotype (QX-like). Amino acid identity among QX-like strains was calculated at 87–100%. A total of 210 predicted amino acid residues were observed, including 31 substitutions and 2 deletions. Conclusions of this study were identified and characterized as GI-19 genotype (QX-like) IBV with amino acid changes on S1 fragment from breeder, broiler, and layer chickens in Java Region.